Outcome Measures Non-Performing Loans on BPR Sejahtera Klaten of Central Java - Riskha Amaliya Lubis; Maryanto Maryanto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
If there are non-performing loans carried out by the debtor, then the bank can take action to overcome the problem loans. In the course of installments in the event of a month (double / substandard), the Bank's officer will make a collection to return smoothly, but in reality the debtor is difficult, to meet with the Bank. Factors that cause the BPR Sejahtera Klaten. Selecting non-litigation pathways in resolving problem loans. Because it saves time, costs, outputs that can be Achieved, approaches with good faith, the ability to pay customers are considered. In taking out credit guarantees, the bad creditors can not enforce coercion Because It is an illegal act. Therefore the problem of bad credit requires a wise solution where the parties do not feel disadvantaged.Keywords: Non-Performing Loans; Wise Settlement.